Challenges and Opportunities in Hybrid Learning: Perspectives from International Students in a University Setting - Drozdova, Valerija (Journal of Education Culture and Society, 2025)
Aim. The aim of the research is to examine the theoretical background, creating a taxonomy for the diverse terminology associated with online teaching and learning, to examine the theoretical foundations of hybrid learning, and to identify the benefits and drawbacks of the hybrid approach to teaching English for Specific Purposes. The present research explores the experiences of Latvian and foreign students studying in a hybrid format at Turiba University, aiming to offer insights into its effectiveness and challenges from an interdisciplinary perspective in the post-pandemic era. Methods. Mixed-method research investigated how students perceive a hybrid style of learning from linguistic, pedagogical, and intercultural perspectives and identify the challenges and benefits observed. Methods included lecture observation, analysis of teaching sessions, questionnaires, and qualitative content analysis. Results. Findings show students value the hybrid learning approach for flexibility, accessibility, and time-saving. However, significant challenges include managing complex, multi-layered communication and unexpected technical disruptions. Linguistically, students faced difficulties with pronunciation and understanding diverse accents, hindering communication. From an intercultural point of view, varying educational styles, expectations, and time zone differences posed challenges. Despite these hurdles, students improved self-confidence, communicative and language skills, as well as cultural awareness, suggesting that with appropriate strategies, this approach can effectively support diverse educational needs in a globalised learning environment. Conclusion. A hybrid learning style, while offering flexibility and accessibility for international students, requires careful preparation, strong motivation, technical readiness, and continuous engagement from both lecturers and students to ensure effective participation and a meaningful learning experience.